The Effects of Digital Economy on Inclusive Growth in Selected African Countries - Dakwal, Solomon Mangut; Okwanya, Innocent; Ogiri, Aisha I. (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: The originality of this work is the inclusion of more variables that are used to develop the digital economy index, which is a more accurate representation of the digital economy in Africa. Also, instead of capturing the inclusive growth with a single variable such as HDI, GDP per capita, or RGDP per person employed, as seen in previous studies, this study adds to the body of literature by creating an inclusive growth index using the four key indicators of inclusive growth.Research Objective: This study investigates the effect of the digital economy on inclusive growth in selected African countries.Research Methods: The study employed longitudinal panel data sourced from the world development indicators and was analyzed using the Arellano and Bond (1991) system Generalized Method of Moments (SGMM), a dynamic panel data model that handles endogeneity, unobserved heterogeneity, and autocorrelation.Empirical Results: The findings demonstrated a positive and significant effect of the digital economy on inclusive growth in the countries studied. The effects of the digital economy are more visible in lower—and lower-middle-income (LI and LMI) countries than in upper-middle-income (UMI) African countries.Implications: These findings imply that improving investments in internet infrastructure and fostering a technology-driven economy can help Africa achieve more robust inclusive growth.JEL Classification: O3, O4, C31